Design of a modeling tool for wheel connected with a belt using speed and time control for video tracker analysis - Sari, Reza Novita; Asrizal, Asrizal; Amir, Harman; Mairizwan, Mairizwan (Journal of Experimental and Applied Physics, 2024)
The influence of the advances of science produces technological innovations that leverage on education, economics, social and self-development. In education, design of laboratory experimental modeling tools continues to be carried out by researchers to improve learning effectiveness. Wheel movement experiments related to belts include one of physic learning activities. The parameter measured from the creation of modeling tool is the wheel speed and analysis of wheel motion related to the belt. The system can be controlled in speed and time using Blynk application. Video recordings are used as circular motion analysis material on Tracker applications. The design of system is a box size 35 cm in length, 20 cm in width and 18 in height consisting of one switch, LCD, and two wheels connected by a belt. Wheel 1 has a diameter of 15 cm and wheel 2 is 10 cm. Based on data analysis, the results of physical parameters were obtained with high accuracy and precision values using standard measuring instruments, namely tachometers, calculation of the theoretical formula. The system's precision was 98.84% and speed accuracy for 30 rpm, 50 rpm and 80 rpm were 99.3%, 99.19% and 99.93%. Frequency values increased according to the increase in input speed and compared to the reverse period.  The angle speed will increase as the wheel spokes become smaller. So, the wheel modeling tool related to the belt using speed and time control with the Blynk application as well as the Tracker video alysis can work effectively and validly.